2009
DOI: 10.1186/1471-2407-9-65
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of Caveolin-1 in hepatocellular carcinoma: correlation with differentiation state, motility and invasion

Abstract: BackgroundCaveolin-1 is the main component of caveolae membrane structures and has different roles during tumorigenesis in different cancer types with varying expression profiles, indicating that the role of caveolin-1 varies according to tumor type. In this study, we investigated the role and expression of caveolin-1 in hepatocellular carcinogenesis.MethodsWe analyzed the expression of Caveolin-1 in 96 hepatocellular carcinoma (HCC), 29 cirrhosis, 20 normal liver tissues and 9 HCC cell lines by immunostaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 33 publications
(34 reference statements)
10
94
2
1
Order By: Relevance
“…However, studies in cancer patients and animal models have shown that in prostate, breast, lung, and pancreatic cancer, an increase in CAV1 expression is correlated with a poor prognosis and reduced survival (47)(48)(49)(50)(51). Several studies have shown a role for CAV1 in tumor invasion and metastasis (52,53). Recent studies in renal cell carcinoma cells showed that HIF-mediated induction of CAV1 expression is correlated with activation of EGFR signaling in a ligand-independent manner (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in cancer patients and animal models have shown that in prostate, breast, lung, and pancreatic cancer, an increase in CAV1 expression is correlated with a poor prognosis and reduced survival (47)(48)(49)(50)(51). Several studies have shown a role for CAV1 in tumor invasion and metastasis (52,53). Recent studies in renal cell carcinoma cells showed that HIF-mediated induction of CAV1 expression is correlated with activation of EGFR signaling in a ligand-independent manner (24).…”
Section: Discussionmentioning
confidence: 99%
“…Cav-1 is a palmitoylated lipid raft protein and has been found to interact with FASN in prostate cancer cells to promote tumor growth and survival (55). Recently, Cav-1 was also reported to promote the motility and invasion of hepatocellular carcinoma (HCC) and metastasis in a mouse model though an unknown mechanism (56,57). We therefore postulate that following HCV infection, FASN interacts with NS5B and, together with Cav-1, is recruited to lipid rafts, followed by the induction of signaling leading to hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Cav-1 Expression-The absence of Cav-1 in well differentiated human HCC has been recently reported to be a specific signature of these cells (31). Accordingly, Cav-1 levels were analyzed in various hepatic cell lines, and although the hepatocytelike THLE-2 or CHL cells showed a significant expression of Cav-1 mRNA and protein, the HCC lines, such as HepG2 or HuH-7, failed to express this gene (Fig.…”
Section: Snon Protein Levels Are Increased In Hcc Human Cells That Lackmentioning
confidence: 99%